Recent Insights into the Contribution of the Changing Hypertrophic Chondrocyte Phenotype in the Development and Progression of Osteoarthritis - Ripmeester, Ellen G. J.; Timur, Ufuk Tan; Caron, Marjolein M. J.; Welting, Tim J. M. (Frontiers in Bioengineering and Biotechnology, 2018)
Osteoarthritis is an extremely prevalent age-related condition. The economic and societal burden due to the cost of symptomatic treatment, inability to work, joint replacement and rehabilitation is huge and increasing. Currently there are no effective medical therapies that delay or reverse the pathological manifestations of osteoarthritis. Current treatment options are, without exception, focused on slowing down progression of the disease to postpone total joint replacement surgery for as long as possible and keeping the associated pain and joint immobility manageable. Alterations in the articular cartilage chondrocyte phenotype might be fundamental in the pathological mechanisms of osteoarthritis development. In many ways the changing chondrocyte phenotype in osteoarthritic cartilage resembles the process of endochondral ossification as seen, for instance, in developing growth plates. However, the relative contribution of endochondral ossification to the changing chondrocyte phenotype in the development and progression of osteoarthritis remains poorly described. In this review we will discuss the current knowledge regarding the cartilage endochondral phenotypic changes occurring during osteoarthritis development and progression, as well as the molecular and environmental effectors driving these changes. Understanding how these molecular mechanisms determine the chondrocyte cell fate in osteoarthritis will be essential in enabling cartilage regenerative approaches in future treatments of osteoarthritis.